Impact of fish feed formulation training on feed use and farmers' income: Evidence from Ghana - Ragasa, Catherine; Mensah, Yaa Osei; Amewu, Sena (Elsevier, 2022)
Feed accounts for 60–80% of tilapia production costs, and high feed cost and limited feed access are major issues faced by fish farmers. A potential solution is for farmers to produce their own feeds using cheaper and locally available ingredients. This paper evaluates the feed formulation training implemented in Ghana as part of the Fisheries Commission's activities under the Ghana Aquaculture for Food and Jobs program. This paper analyzes baseline and follow-up survey data using difference-in-difference estimation and analysis of covariance. One year after the training, results show positive impact on the farmers' knowledge of feed formulation, quantity of feed formulated, feeding and management practices, productivity, and income. Feed formulation training encouraged more farmers to formulate their own feeds and maintained or increased total feeds used in their facilities from 2018/2019 to 2020/21. Among the farmers who did not receive training, feed formulation activities and feed quantity used reduced from 2018/19 to 2020/21. A common practice is the use of locally available quality commercial feed as starter feed for smaller fish and own-formulated feeds as a complement for or alternative to commercial growout feeds for bigger fish. Especially when constrained by lack of funds, many farmers reduce the use of commercial feeds and formulate their feeds using cheaper and locally available raw materials to maintain similar levels of feeding intensity. Feed formulation acts as an important coping strategy in the context of small-scale farmers with limited financial resources. This study recommends scaling out feed formulation training and expanding research on optimal fish nutrition using locally available and low-cost raw materials, in combination with commercial feeds to maximize productivity and incomes for farmers.